The Effect of Written Retelling Technique on Students’ Reading Comprehension Across Personality Learning Styles - Damiri, Sylvia; Widiati, Utami (citeus, 2017)
This quasi experimental study aims to investigate how written retelling technique affects the reading comprehension of university students having different personality learning styles (introverted vs. extroverted). A reading comprehension test and a questionnaire were utilized to collect the data. Two groups of students were involved in the study, with the experimental group receiving the treatment of being taught using a written retelling technique and the control group being taught using the oral retelling technique. The results of the study revealed that the first group of students showed better performance in reading comprehension test than the latter group. Even though there was a significant difference between the extroverted and the introverted students in reading comprehension achievement, the findings suggest that written retelling technique was more effective regardless of the personality learning styles.